Short-Term Results of Shoulder Instability Surgery - Erhan Bayram; Ahmet Kamil Ertürk; Cem Yıldırım; Doğan Atlıhan; Mahmut Ercan Çetinus; Murat Yılmaz (Haseki Tıp Bülteni)
Aim: In this study, we aimed to discuss the result of arthroscopic surgery for shoulder instability and we planned to show the value of instability tests for determining success of surgery.